PUBLIC EXPENDITURE ON EDUCATION FINANCED FROM LOCAL BUDGETS - Cristinel, Ichim (Ecoforum Journal, 2017)
In this article we intend to analyze and deepen an important category of expenditure funded from local budget, namely the expenditure on education. Our scientific approach starts with establishing the place of these expenses within the local public expenditures by specifying their content and role. A special place within the article deals with the treatment of the particularities of the financing of the pre-university education units from the local budgets. The research is based on the quantitative analysis of expenses for education from local budgets, based on the data in the Romanian Statistical Yearbook and highlights the place this category of expenses occupies within the public expenditures in the local budgets as well as their dynamics. Research shows that the evolution and structure of education expenditures financed from local budgets is determined by the action of variables that differ from one territorial administrative unit to another: the specifics of the training, the urban / rural environment, the number and social structure of the population, enrollment of school-age population in some form of education. Research shows that between 1995 and 2015 the dynamics of the share of education expenditures in the total expenditure in local budgets is marked by the legal regulations regarding the financing of state pre-university education institutions.